THE INFLUENCE OF FINANCIAL INSTITUTIONS ON THE GROWTH OF THE MICRO AND SMALL AGRIBUSINESS INDUSTRY IN INDONESIA - Syalma Nabila Kamal; Dwi Rachmina; Feryanto Feryanto (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2023)
Agribusiness micro and small industries (MSI) have contributions in economic and social aspects. Financial institutions provide facilities and products to increase the accessibility of capital for Agribusiness MSIs. This study aims to analyze the influence of banks and non-bank financial institutions on the growth of micro and small food and non-food agribusiness industries. This study uses secondary data from potential village surveys in 2018 and 2022 with 82,900 villages in Indonesia annually. Data were analyzed using the Fixed Effect Model in Stata 15.0 software. The results show that four variables significantly positively affect Agribusiness MSIs: non-bank financial institutions (savings and loan cooperatives), electricity index, infrastructure and distribution index, and telecommunications and information index. The disaggregation results based on Agribusiness MSIs sector (food and non-food) show that the food and non-food agribusiness MSIs is positively and significantly influenced by non-bank financial institutions (saving and loan cooperative), the electricity index, as well as the telecommunication and information index. However, bank financial institutions, as well as infrastructure and distribution indexes, only have a significant positive effect on non-food Agribusiness MSIs. Alternative to increasing the number of Agribusiness MSIs units can be done with government support through policies to optimize the role of cooperatives and distribute infrastructure, especially related to telecommunications and information.